DEVELOPMENT OF SOCIAL SKILLS IN LEARNING SOCIAL STUDIES IN PRIMARY SCHOOL - Nurlaila, Nurlaila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
Referring to the standard social studies curriculum content subjects, 2006, one of the competencies that would be developed is to give students with a useful social knowledge, social skills, and intellectual, in fostering social attention as well as human resources who care as good Indonesian citizen and responsible realize national goals. To be able to successfully learn social studies, students should be equipped not only knowledge, but also the need to be explored and developed dimension of the skills and attitude value. Therefore, the focus of discussion in this paper is the urgency to develop social skills that are integrated into social studies teaching in elementary school. Processes and learning outcomes with social skills and building value is needed to equip learners to anticipate the future challenges that certainly will be more severe and complex. Teachers as curriculum developers are demanded to be skillful to bring atmosphere and learning activities which has purpose on developing basic skills and the cultivation and development of personality, temperament and character.. Implementation of educational based on social skills and coaching will is believed have valuable graduates outcome that have personality, temperament and good character. Therefore, the main task of basic education is to build students' character and have purpose build students from an early age in order to not fail be a perfect human.